Effect of Duration and Temperatur Breastmilk Storage and The way of Diluting Breastmilk on Protein and Fat Levels in Breastmilk - Mandria Yundelfa; Mayetti Mayetti; Nur Indrawaty Lipoeto (Journal of Midwifery, 2018)
Exclusive breastfeeding is the best method of nutrition for infant to grow and develop. Changes in social often make women become to work increased from 50.77% (2016) to 50.89% (2017), so they think there is no time to give exclusive breastfeeding to her baby. But with the storage of breast milk, the baby will still get breast milk when the mother is at work. This study aims to determine the effect of duration and temperature of breastmilk as well as how to dilute frozen milk to protein and fat levels. The design of this study was one group pretest-posttest design with the pre experimental study. The data were analyzed by using T-dependent test. The sample of this study is breast milk obtained from 5 breastfeeding mothers in the work area of LubukBuaya Public Health and Laboratory Animal Biotechnology of Andalas University in July in 2017 to May in 2018.There was significant decrease mean of protein and fat content in breastmilk during 5 days storage at refrigerator that mean of protein content 0,50±0,44 g/dL and fat content 2,57±0,45 g/dL statistically (p<0,05). There  was no significant decrease in the mean of protein and fat content in breast milk, which was dissolved in refrigerator and warm water is average protein content 0.89±0.46 g/dL and mean fat content 3.21±0.19 g/dL, direct melted breastmilk with mean of protein content is 0.91±0.52 g/dL and mean of fat content is 3.05±0.25 g/ dL statistically (p>0.05). The conclusion, there is no effect of protein and fat content in breast milk storaged for 4 hours in the room temperature, 14 days in freezer (-15 C), 28 days in freezer (-18 C) and how to dilute frozen milk. But there is adecrease  on the levels of protein and fat in breast milk in 5-day storage in the refrigerator.